2004
DOI: 10.1098/rstb.2003.1372
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic recombination hot spots and human DNA diversity

Abstract: Meiotic recombination plays a key role in the maintenance of sequence diversity in the human genome. However, little is known about the fine-scale distribution and processes of recombination in human chromosomes, or how these impact on patterns of human diversity. We have therefore developed sperm typing systems that allow human recombination to be analysed at very high resolution. The emerging picture is that human crossovers are far from randomly distributed but instead are targeted into very narrow hot spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 38 publications
(67 reference statements)
4
68
0
Order By: Relevance
“…Fungicide application is a common practice in canola and potato production systems, whereas fungicides are usually not applied in pea and lentil cropping systems. Thus, a combination of ecological, molecular and evolutionary forces such as mutation events, natural selection, genetic drift, population bottleneck and migration in different populations could explain the lack of linear relationship between LD and the distance on a chromosome in all the populations studied (Jeffreys et al, 2004;Hsueh et al, 2006). For example, low levels of polymorphisms at certain loci (because of population bottleneck) could reduce the chance of detecting crossover.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fungicide application is a common practice in canola and potato production systems, whereas fungicides are usually not applied in pea and lentil cropping systems. Thus, a combination of ecological, molecular and evolutionary forces such as mutation events, natural selection, genetic drift, population bottleneck and migration in different populations could explain the lack of linear relationship between LD and the distance on a chromosome in all the populations studied (Jeffreys et al, 2004;Hsueh et al, 2006). For example, low levels of polymorphisms at certain loci (because of population bottleneck) could reduce the chance of detecting crossover.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that this DNA region of the chromosome 5 had some level of recombination or high mutation rate, as seven of the eight populations showed linkage equilibrium between markers 19A and 19B (Table 3). Recombination hot spots have been detected in the human genome (Chakravarti et al, 1984;Ardlie et al, 2002;Arnheim et al, 2003;Jeffreys et al, 2004), and also found in many other genomes including Cryptococcus spp. (Hsueh et al, 2006), P. falciparum (Mu et al, 2005) and Schizosaccharomyces pombe (Steiner and Smith, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSRs, being recombination hot spots aid in genome evolution, sometimes being the basis of diseases [10,11]. Functionally, these sequences are reported to be associated with gene regulation, transcription and protein function [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative technique of sperm typing, which allows for many thousands of meiotic products to be screened from a single individual, produces extremely high-resolution estimates. However, these studies are male-specific, are typically only applied to a few individuals and are currently limited in scale to only small (<1 Mb) regions of the genome (Arnheim et al 2003;Jeffreys et al 2004;Greenawalt et al 2006).…”
mentioning
confidence: 99%